Uji Organoleptik Jus Susu Kurma (Phoenix Dactylifera L.) Sebagai Minuman Energi Ibu Bersalin - Ulya, Yadul; Maya Herlina, Siskha; Pricilia Yunika, Regina (Journal of Fundus, 2023)
Background: The nutritional needs of birthing mothers can be met by providing nutrition in liquid form that is easy to digest, quickly converted into energy, delicious, practical, and suitable for the condition of the birthing mother, one of which is juice. Organoleptic/sensory testing of date milk juice plays an important role as an initial detection in assessing quality to identify deviations and changes in the product. Objective: This research aims to determine consumer acceptance and preference for date milk juice products. Methods: This research is a type of experimental research by conducting an organoleptic test, namely testing the panelists' preferences for the product being tested using a hedonic scale which is transformed into a numerical scale. Organoleptic tests were carried out on 30 panelists on date milk juice products with color, taste, aroma and texture parameters. Results: The organoleptic test results for the date milk juice product were found to have an average numerical scale that was not much different so that the hedonic scale produced was still in the range preferred by the panelists. Conclusions: It is hoped that mothers in labor can consume date milk juice (phoenix dactylifera L.) easily, practically and deliciously as an alternative effort to fulfill the energy needs of mothers in labor to facilitate labor